The entanglements which make instruments musical: Rediscovering sociality. Issue 2 (15th March 2021) - Waters, Simon
Abstract : A thing becomes a musical instrument by virtue of its use in a social context, a use of which its initial intended design (if it had one) forms only a part: sometimes a very small part. Drawing on the notion of the 'performance ecosystem' this papersuggests that instrument designers/makers working with digital technologies might fruitfully attend further to the social contexts/constructs that characterise every level of musicking. It looks at the emergent, situated co-development of player, instrument and environment, suggesting that humans habitually use instruments to sense out, test and probe the possibilities of self-other relations in dynamic, mutually-engaging, and often playful and improvised behaviours. 1